Perturbation of the mutated EGFR interactome identifies vulnerabilities and resistance mechanisms. Issue 1 (5th November 2013) - Li, Jiannong; Bennett, Keiryn; Stukalov, Alexey; Fang, Bin; Zhang, Guolin; Yoshida, Takeshi; Okamoto, Isamu; Kim, Jae‐Young; Song, Lanxi; Bai, Yun; Qian, Xiaoning; Rawal, Bhupendra; et al.
Abstract : We hypothesized that elucidating the interactome of epidermal growth factor receptor (EGFR) forms that are mutated in lung cancer, via global analysis of protein–protein interactions, phosphorylation, and systematically perturbing the ensuing network nodes, should offer a new, more systems‐level perspective of the molecular etiology. Here, we describe an EGFR interactome of 263 proteins and offer a 14‐protein core network critical to the viability of multiple EGFR‐mutated lung cancer cells. Cells with acquired resistance to EGFR tyrosine kinase inhibitors (TKIs) had differential dependence of the core network proteins based on the underlying molecular mechanisms of resistance. Of the 14 proteins, 9 are shown to be specifically associated with survival of EGFR‐mutated lung cancer cell lines. This included EGFR, GRB2, MK12, SHC1, ARAF, CD11B, ARHG5, GLU2B, and CD11A. With the use of a drug network associated with the core network proteins, we identified two compounds, midostaurin and lestaurtinib, that could overcome drug resistance through direct EGFR inhibition when combined with erlotinib. Our results, enabled by interactome mapping, suggest new targets and combination therapies that could circumvent EGFR TKI resistance. Abstract : A 'lung cancer'‐specific mutant EGFR interactome was generated by a global analysis of protein–protein interactions and phosphorylation. After functional screening, nine proteins were identified as essential for the viability of EGFR‐mutant lung cancer cells. Synopsis: A 'lung cancer'‐specific mutant EGFR interactome was generated by a global analysis of protein–protein interactions and phosphorylation. After functional screening, nine proteins were identified as essential for the viability of EGFR‐mutant lung cancer cells. The interactome of lung cancer‐associated mutant forms of epidermal growth factor receptor (EGFR), consisting of 263 proteins, was built by integrating protein–protein interactions and tyrosine phosphorylation. Systematic perturbations of the network nodes revealed a core network of 14 proteins, 9 of which were shown to be specifically associated with survival of EGFR‐mutant lung cancer cells. Cells with acquired resistance to EGFR tyrosine kinase inhibitors showed differential dependence on the core network proteins. A drug network associated with the core network proteins led to the identification of two compounds, midostaurin and lestaurtinib, that could overcome drug resistance through direct EGFR inhibition when combined with erlotinib.